Constraints of Small and Medium Food Industry to Take Advantage of Domestic Market Opportunities during the Covid-19 Pandemic - M. Taneo, Stefanus Yufra; Noya, Sunday; Setiyati, Etsa Astridya; Melany, . (KnE Social Sciences, 2021)
The small and medium-sized food industry (SMFI) has a great opportunity to meet domestic market demand during the Covid-19 pandemic but there are various obstacles. This paper aims to present the constraints faced by SMFIs, especially concerning raw materials and marketing, in taking advantage of domestic market opportunities, and proposes alternative solutions. The study was conducted on four SMFIs that produce functional food in Malang Regency. Data were collected through in-depth interviews. The results showed that the demand for functional foods such as garlic, ginger, turmeric and fruits increased during the Covid-19 pandemic, which seemed to be related to public awareness about increasing immunity. However, the obstacles faced by SMFIs were the high price of raw materials due to limited supply, and limited marketing because they did not have distribution licenses from BPOM. Information about the process and BPOM’s distribution permit requirements was very limited for SMFI managers, and large capital was needed to fulfill the requirements of Good Manufacturing Practices. Therefore, SMFIs should have long-term cooperation with farmers to ensure the availability of raw materials; build networks and maintain cooperation with customers; and utilize credit for MSMEs in the economic recovery program provided by the government to meet the GMP requirements in BPOM’s distribution permit. The government should conduct intensive outreach to SMFI managers about the process and requirements for distribution permits from BPOM, credit facilities, and other policies related to economic recovery during the Covid-19 pandemic. Keywords: small and medium food industry, domestic market, Covid-19 pandemic, BPOM